2019
DOI: 10.3390/app9112367
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Luminescent Properties of Zn–Cu–In–S/ZnS Quantum Dot Films under UV Excitation

Abstract: Quantum dots (QDs) are quite interesting materials due to their unique chemical and physical properties. ZnCuInS/ZnS QDs can be produced either in hydrophobic or hydrophilic form, are non-toxic, and thus favorable for studies in the area of biology. Poly(methyl methacrylate) (PMMA) is a well-known biocompatible resin which is widely used in dentistry, ophthalmology, and orthopedic surgery. Four composite PMMA films of ZnCuInS/ZnS nanocrystals with maximum emission at 530 nm and concentrations of 1.0, 4.0, 6.0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…For the semiconducting QDs, hydrophobic green‐emitting Zn–Cu–In–S/ZnS (ZCIS/ZnS) core/shell QDs were investigated. [ 59 ] A well‐dispersed suspension of ZCIS/ZnS QDs in chloroform was single inkjet printed on prepared substrates at 200 dpi using an inkjet nozzle with an orifice diameter of 50 μm, after which the printed QD spot patterns were investigated using the optical microscope and the 3D surface profiler.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the semiconducting QDs, hydrophobic green‐emitting Zn–Cu–In–S/ZnS (ZCIS/ZnS) core/shell QDs were investigated. [ 59 ] A well‐dispersed suspension of ZCIS/ZnS QDs in chloroform was single inkjet printed on prepared substrates at 200 dpi using an inkjet nozzle with an orifice diameter of 50 μm, after which the printed QD spot patterns were investigated using the optical microscope and the 3D surface profiler.…”
Section: Resultsmentioning
confidence: 99%
“…These uniform distributions and the distinctive height profiles for the inkjet‐printed ZCIS/ZnS QDs in the P4VP layer are clear evidence of the formation of the microinlaid QD spot structure via the selective spatial etching of P4VP and the simultaneous uniform filling of QDs, similar to the inkjet‐inlaid CBP spots in P4VP shown earlier. In contrast, when ZCIS/ZnS QD spots were inkjet printed on a phase‐inseparable PMMA layer, [ 59 ] the observed height profiles of the QD spots on the PMMA layer were quite different from those of the microinlaid QD spots on P4VP. The printed QD spots on the PMMA layer showed dome‐shaped and plateau‐type height profiles (diameter: ≈90 nm, height: ≈20 nm), analogous to those of QD spots on a bare glass substrate (diameter: ≈80 nm, height: ≈15 nm, Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The K-shell energy peak, corresponding to the enhanced photoelectric absorption, is observed at approximately 28 keV. The inset in Figure 2 shows the normalized luminescence spectrum of the examined QDs [46].…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Shen et al demonstrated high-performance QLEDs that emit three primary colors; they reported maximum external quantum efficiencies of 21.6, 22.9, and 8.05% for red, green, and blue-emitting QLEDs, respectively [5]. However, due to the restriction of hazardous substances compliance in Europe, the substitution of Cd-based QDs with eco-friendly materials has become an important task for electroluminescence (EL) devices Therefore, several options such as indium phosphide and Cu-In-S based QDs have been studied recently [6,7]. Additionally, in the sequential formation of various thin films of EL devices, solution processes lead to less stable films than in the high-vacuum processes owing to the inevitable influence of the organic solvents used in the solution process on the underlying layers.…”
Section: Introductionmentioning
confidence: 99%